Purification of cell‐derived Japanese encephalitis virus by dual‐mode chromatography. (11th June 2020) - Zhang, Fuliang; Luo, Jun; Teng, Man; Xing, Guangxu; Guo, Junqing; Zhang, Yihua
Abstract: Purification of the enveloped virus poses a challenge as one must retain viral infectivity to preserve immunogenicity. The traditional process of virus purification is time‐consuming, laborious and hard to scale up. Here, a rapid, simple and extensible laboratory program for the purification of Japanese encephalitis virus (JEV) was developed by using differential centrifugation, ultrafiltration, Sepharose 4 fast flow gel chromatography, and Capto TM Core 700 chromatography. The entire process recovered 61.64% of the original virus, and the purified virus particles maintained good activity and immunogenicity. The purification process described has potential application in large‐scale production of high‐purity JEV. Abstract : Comparison of different purification mehods of Japanese Encephalitis Virus. A rapid, simple and extensible laboratory program for the purification of Japanese encephalitis virus was developed by using differential centrifugation, ultrafiltration, Sepharose 4 fast flow gel chromatography and CaptoTM Core 700 chromatography. The purified virus particles maintained good activity and immunogenicity.